Influence of the substrate in germination of lychee seeds - Andrade, Renata Aparecida de [UNESP]; Martins, Antonio Baldo Geraldo [UNESP]; Oliveira, Inez Vilar de Morais [UNESP] (Sociedade Brasileira de Fruticultura, 2004)
A lichia é considerada em todo o mundo como a rainha das frutas, por sua aparência e sabor delicado. Atualmente, a cultura vem despertando interesse, principalmente no Estado de São Paulo, onde, em virtude dos problemas enfrentados pelos agricultores, destacando-se os de laranja e cana-de-açúcar, a procura por alternativas agrícolas vem se intensificando ainda mais. A propagação através de sementes não é recomendada comercialmente, pois as plantas de pé-franco são geneticamente muito desuniformes e apresentam período juvenil muito longo, demorando até 10 anos para entrar em produção; no entanto, a semente pode ser utilizada para a obtenção de porta-enxertos. Observou-se que a germinação de sementes de lichia ocorre rapidamente, reforçando a importância do uso de um substrato adequado. Pela análise dos resultados obtidos, verifica-se que o substrato que aparentemente permitiu as melhores combinações de água e disponibilidade de oxigênio para as sementes - casca de arroz carbonizada e areia lavada, foi o que proporcionou valores de germinação mais rápidos e mais altos.

The lychee is, all over the world, considered as the queen of the fruits due to the delicacy of its appearance and flavor. Although it was only recently that it started to have economical importance in Brazil, the lychee is already calling the attention of numerous farmers, mainly those who cultivate citric fruits and/or sugarcane in the State of São Paulo, due to the constant and at the same time growing necessity of finding new alternative crops. Considering that the commercial cultivation of lychee plants in the field requires the previous obtainment of rootstocks viewing to reduce the genetic variability and the length of the juvenile period displayed by plants resulting directly from the seeds, finding ways to improve the germination performance of lychee seeds for the production of rootstock plants is of considerable economic importance. Thus, the objective of this experiment was to test five substrates for the germination of lychee seeds: (1) vermiculite, (2) washed sand, (3) filter paper, (4) carbonized rice hull, and (5) sphagnum. The results showed that the period of time required by a lychee seed to germinate is a short one thus reinforcing the importance of providing a suitable substrate for the germination to take place. It was found that the substrates which apparently allowed the best combinations of water and oxygen availability for the seeds - washed sand and carbonized rice hull - were those leading to the fastest and highest germination values.
Influência do substrato na germinação de sementes de lichia
Keywords: Litchi chinensis Sonn; Seed; Germination; Litchi chinensis Sonn.; Sementes; Germinação